2022
DOI: 10.3390/ijms232214264
|View full text |Cite
|
Sign up to set email alerts
|

The Synergistic Effect of Adsorption-Photocatalysis for Removal of Organic Pollutants on Mesoporous Cu2V2O7/Cu3V2O8/g-C3N4 Heterojunction

Abstract: Cu2V2O7/Cu3V2O8/g-C3N4 heterojunctions (CVCs) were prepared successfully by the reheating synthesis method. The thermal etching process increased the specific surface area. The formation of heterojunctions enhanced the visible light absorption and improved the separation efficiency of photoinduced charge carriers. Therefore, CVCs exhibited superior adsorption capacity and photocatalytic performance in comparison with pristine g-C3N4 (CN). CVC-2 (containing 2 wt% of Cu2V2O7/Cu3V2O8) possessed the best synergist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…It was another evidence to indicate that the photogenerated carrier separation efficiency of 10%SVC was higher than that of CN. 59 It could therefore effectively enhance photocatalytic degradation activity of LVX.…”
Section: Resultsmentioning
confidence: 99%
“…It was another evidence to indicate that the photogenerated carrier separation efficiency of 10%SVC was higher than that of CN. 59 It could therefore effectively enhance photocatalytic degradation activity of LVX.…”
Section: Resultsmentioning
confidence: 99%
“…Although the effectiveness of nano-adsorbents in removing organic compounds is remarkable, there are limitations to the use of conventional materials, such as separation from aqueous media and recycling using nano-adsorbents and nano-catalysts [ 152 ]. Feng et al [ 153 ] utilized a reheating preparation approach to fabricate Cu 2 V 2 O 7 /Cu 3 V 2 O 8 /g-C 3 N 4 heterojunctions (CVCs). A higher surface area was obtained via the thermal etching process.…”
Section: Wastewater Treatmentmentioning
confidence: 99%
“…The CVCs showed excellent adsorption and photocatalysis activities. It was found that CVC-2 comprising of 2 wt% of Cu 2 V 2 O 7 /Cu 3 V 2 O 8 exhibited higher levels for the removal of different dyes and antibiotics; (96.2%) of methylene blue (MB), (97.3%) of rhodamine B (RhB), (83%) of ciprofloxacin (CIP), (86%) of tetracycline (TC), and (80.5%) of oxytetracycline (OTC) were removed via the adsorption and photocatalysis performance under visible light irradiation [ 153 ].…”
Section: Wastewater Treatmentmentioning
confidence: 99%
“…In this Special Issue, Feng et al reported that the synergistic effect of adsorptionphotocatalysis for the removal of organic pollutants on mesoporous Cu 2 V 2 O 7 /Cu 3 V 2 O 8 /g-C 3 N 4 heterojunctions (CVCs) enhanced visible light absorption and improved the separation efficiency of photoinduced charge carriers [18]. CVCs exhibited superior adsorption capacity and photocatalytic performance in comparison with pristine g-C 3 N 4 (CN) CVC-2 (containing 2 wt% of Cu 2 V 2 O 7 /Cu 3 V 2 O 8 ) [18]. Good synergistic removal efficiencies were obtained for dyes (96.2% for methylene blue, 97.3% for rhodamine B) and antibiotics (83.0% for ciprofloxacin, 86.0% for tetracycline and 80.5% for oxytetracycline) [18].…”
mentioning
confidence: 99%
“…CVCs exhibited superior adsorption capacity and photocatalytic performance in comparison with pristine g-C 3 N 4 (CN) CVC-2 (containing 2 wt% of Cu 2 V 2 O 7 /Cu 3 V 2 O 8 ) [18]. Good synergistic removal efficiencies were obtained for dyes (96.2% for methylene blue, 97.3% for rhodamine B) and antibiotics (83.0% for ciprofloxacin, 86.0% for tetracycline and 80.5% for oxytetracycline) [18]. The pseudofirst-order rate constants of methylene blue and rhodamine B photocatalytic degradation on CVC-2 were 3 times and 10 times that of pristine g-C 3 N 4 .…”
mentioning
confidence: 99%